TEACHING AUTHENTIC READING MATERIALS FOR HIGH LEVEL STUDENTS - Rakhimakhon Tursunova Valijonovna (TADQIQOTLAR, 2025)
Annotation. This article explores effective methods of teaching reading using authentic materials for high-level students. Authentic texts, taken from real-life sources, help learners develop natural language use, critical thinking, and communicative competence. The study also discusses how teachers can select and apply authentic materials in class to enhance vocabulary, motivation, and comprehension skills.